Implementasi Laporan Divisi Keuangan Berdasarkan Standar Operasional Perusahaan pada PT. Indo Spicies Trading, Sukabumi - Reynold Gustaf; Lia Liliawati; Aghniya Nadira Zahrotu Nissa (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This study aims to design a Standard Operating Procedure (SOP) in the Finance Division of PT Indo Spices Trading, located in Sukabumi Regency. SOP is an important guideline that ensures that all of the company's financial activities run systematically, efficiently, and in accordance with accountability standards. In this study, the method used is a qualitative descriptive approach with data collection through observation, interviews, and internal company document studies. The results of the study indicate that the implementation of SOP in the Finance Division can improve the effectiveness of the administration process, reduce the risk of errors in financial recording, and strengthen supervision and transparency. The designed SOP includes cash management procedures, financial reporting, operational cost control, and internal audit implementation. With this SOP, it is hoped that PT Indo Spices Trading will be able to improve better financial governance and support the growth and sustainability of the company in accordance with the vision of "Grow Together, Successfully Together."